2016
DOI: 10.1007/s00259-016-3494-2
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of FET PET at radiotherapy planning in newly diagnosed glioblastoma

Abstract: BackgroundGlioblastoma patients show a great variability in progression free survival (PFS) and overall survival (OS). To gain additional pretherapeutic information, we explored the potential of O-(2-18F-fluoroethyl)-L-tyrosine (FET) PET as an independent prognostic biomarker.MethodsWe retrospectively analyzed 146 consecutively treated, newly diagnosed glioblastoma patients. All patients were treated with temozolomide and radiation therapy (RT). CT/MR and FET PET scans were obtained postoperatively for RT plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 30 publications
2
34
1
3
Order By: Relevance
“…Justin et al proposed that performing maximum tumor resection according to findings on T2 and FLAIR images was associated with better prognosis in low-grade glioma [41]. Sidsel et al found that a large tumor volume on FET-PET was an independent predictor of poor survival in GBM patients [42]. The postoperative tumor volume, when based on FET-PET, has also been shown a significant impact on prognosis in GBM patients [39].…”
Section: Discussionmentioning
confidence: 99%
“…Justin et al proposed that performing maximum tumor resection according to findings on T2 and FLAIR images was associated with better prognosis in low-grade glioma [41]. Sidsel et al found that a large tumor volume on FET-PET was an independent predictor of poor survival in GBM patients [42]. The postoperative tumor volume, when based on FET-PET, has also been shown a significant impact on prognosis in GBM patients [39].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical indications in oncology (Figs. 8, 9, and 10) Diagnosis of central nervous system tumours (very low background in healthy brain) (Galldiks et al 2015;Albert et al 2016;Unterrainer et al 2016;Kunz et al 2011;Poulsen et al 2017).…”
Section: Scan Acquisitionmentioning
confidence: 99%
“…Moreover, the amount of residual tracer uptake in FET PET after surgery/prior to chemoradiation of glioblastomas (FET PET performed within 7–20 days after surgery) has a strong prognostic influence, even after adjustment by multivariate survival analyses for the effects of treatment, MGMT promoter methylation and other patient and tumor-related factors (Piroth et al, 2011a, Poulsen et al, 2016, Suchorska et al, 2015). These data indicate that resection of malignant gliomas guided by amino acid PET may increase the amount of neoplastic tissue removed, potentially improving patient outcome.…”
Section: Local Treatment Optionsmentioning
confidence: 99%